Ckobicby Hmd Sdn. Bhd - John Johnny, Laurian; Mohammad, Saidah; Mansor, Muhammad Nazrin; Molek, Filletus (2014)
Ckobicby HMB company is a new company in Suria Sabah, kota kinabalu area. The company provide range of biscuit product in kota kinabalu. It is the goal of the company management to acquire local market share in the bookstore industry through a strong selection of products and services that gives great taste and quality to our customer. Ckobicby HMB Company is a partnership corporation. The company is a jointly owned by Laurian John Johnny, Filletus Molek, SaidahBinti Mohammad, and Muhd. Nazrin Bin Mansur. The shop will bedocated in suria sabah where it is well known as the shopping mall and place for family and tourist and it is also strategicly at the centre of city. Our facility is a rented shop lot and has enough space to accommodate our business layout. The company will offer range of biscuit that are unique inspired from the flower. However the first product is the Tulip Biscuit where as it is a combination of modern and tradiotional element that are the main theme of the company. This tasty and delicious biscuit provide great taste of peanut butter with cute design of Tulip. We not only concentrate retailing but also manucfature. Where we supply the product to retailer and then sell it to customer. We also provide transfortation services for those retailer that have no car. The food and beverages especially in biscuit industry in Sabah is yet to be fully explored. The market is dominated by local, small stores and regional chains. With branded and well known commercialize company such as munchy and julie's biscuit that also have peanut flavour biscuit in modern style, we are trying to differentiate our product with the existing product here in sabah. This will be a challenge to compete with such branded company as competitors. Our start-up expenses come to RM400, 000.00, which is contributed from each of the jointly owner of the company and there is assets contributed from each of the owners. We are expecting to be operating at a loss for the first couple of months of business before advertising take effect and draw in customers.